Inclination angles during cross-slope roof walking. (December 2020) - Breloff, Scott P.; Carey, Robert E.; Wade, Chip; Waddell, Dwight E.
Highlights: Center of mass – lateral ankle inclination angles useful in various settings. Cross-slope walking dramatically changed dynamic stability in healthy subjects. Increased sagittal plane instability may lead to bigger slip risk. Increased frontal plane instability may lead to larger fall risk. Abstract: Residential roofers have the highest rate of falls in the construction sector with injuries and fatalities costing billions of dollars annually. The sloped roof surface is the most predominant component within the residential roof work environment. Postural stability on a sloped work environment is not well studied. Calculating inclination angles (IAs) using the lateral ankle marker could be a quality measure to determine how cross-slope roof walking will influence stability. Will cross-slope roof-walking effect anterior-posterior (AP) and medial–lateral (ML) IAs in adult males? Eleven adult males participated in two testing sessions—level and cross-slope roof gait session on a 6/12 pitched roof segment. Changes in AP and ML IAs between conditions were compared at: heel strike (HS) and toe off (TO). Legs were analyzed separately due to the cross-slope walking. The left foot was 'higher' on the sloped roof and the right was 'lower.' Significant increases (p ≤ 0.006) in IAs were observed due to the sloped roof in all conditions except the AP 'lower' leg (p = 0.136). Increases in IA suggest a decrease in postural stability as the body will result in greater sway compared to a natural posture. Increases in AP IAs may cause slipping in the anterior or posterior direction as the normal force will decrease during HS and TO. In the ML direction, fall risk is increased and more stress is placed on the hip abductors in order to reduce falling. Thus traversing a sloped roof surface reduces stability of healthy workers and escalates injury/fall risk factors.